Phytosterol esters formation from cocoa shell waste and jatropha seeds oil (CSW-TJO) - Siti Nurul Najiah, Abd Rasid (2017)
Phytosterol ester from esterification phytosterol from plant source such as cocoa shell waste and jatropha oil methyl ester have attracted great interest as a new source since the conventional source which is from edible source was not relevant in present due to its shortage. Moreover, the urgent needs of phytosterols ester in various field industries especially in medical and food industries has forced large production of sterol ester. This research was aimed to produce phytosterols ester from cocoa shell waste and Jatropha il in the presence of solid catalyst (treated egg shell) and to investigate the effect of reaction time, reaction temperature and molar ratio of oil extracted from cocoa shell waste and jatropha oil. The practical study was carried out by using UAE-HD to extract phytosterol from cocoa shell waste and two-stage transesterfication method to extract methyl ester from the jatropha oil. Two-stage transesterfication is the suitable method used to reduce high free fatty acid content in jatropha oil and increase the methyl ester yield. Based on this research studies the highest yield of phytosterol was 0.001099274% and the optimum parameter for production of phytosterol ester was at reaction time 5 hours, temperature of 70ºC and ratio (cocoa shell waste oil to methyl ester) of 1:3.